Plasmid encoding matrix protein of vesicular stomatitis viruses as an antitumor agent inhibiting rat glioma growth in situ - Zhang, H.; Wen, Y.J.; Mao, B.Y.; Gong, Q.Y.; Qian, Z.Y.; Wei, Y.Q. (Experimental Oncology, 2007)
Aim: Oncolytic effect of vesicular stomatitis virus (VSV) has been proved previously. Aim of the study is to investigate glioma inhibition effect of Matrix (M) protein of VSV in situ. Materials and Methods: A recombinant plasmid encoding VSV M protein (PM) was genetically engineered, and then transfected into cultured C6 gliomas cells in vitro. C6 transfected with Liposome-encapsulated PM (LEPM) was implanted intracranially for tumorigenicity study. In treatment experiment, rats were sequentially established intracranial gliomas with wild-typed C6 cells, and accepted LEPM injection intravenously. Possible mechanism of M protein was studied by using Hoechst staining, PI-stained flow cytometric analysis, TUNEL staining and CD31 staining. Results: M protein can induce generous gliomas lysis in vitro. None of the rats implanted with LEPM-treated cells developed any significant tumors, whereas all rats in control group developed tumors. In treatment experiment, smaller tumor volume and prolonged survival time was found in the LEPM-treated group. Histological studies revealed that possible mechanism were apoptosis and anti-angiogenesis. Conclusion: VSV-M protein can inhibit gliomas growth in vitro and in situ, which indicates such a potential novel biotherapeutic strategy for glioma treatment. Цель: изучить способность матриксного протеина (М протеина) вируса везикулярного стоматита (ВВС) угнетать рост глиомы
in situ. Материалы и методы: сконструирована рекомбинантная плазмида, кодирующая М протеин ВВС, которая затем была
трансфецирована в культивированные клетки глиомы С6 in. Клетки глиомы С6, трансфецированные инкапсулированным
в липосомы М протеином (ЛИМП), имплантировали интракраниально для изучения туморогенности. В эксперименте крысам
с трансплантированной интракраниально глиомой С6 (исходный штамм) внутривенно вводили ЛИМП. Апоптотическое действие
М протеина на опухолевые клетки изучали с применением флуоресценцентной микроскопии (окрашивание по Хехсту),
проточной цитометрии (окрашивание пропидиумом йодидом), TUNEL васкуляризацию опухоли оценивали гистологически и васкуляризацию опухоли оценивали гистологически и
иммуногистохимически с применением анти-CD31 моноклональных антител. 31 моноклональных антител. 31 моноклональных антител. Результаты: М протеин может индуцировать
лизис клеток глиомы in. Ни у одного животного с трансплантированными клетками глиомы, обработанными ЛИМП,
не возникали опухоли значительного размера, тогда как у всех крыс из контрольной группы опухоли развивались. В группе
животных, которым вводили ЛИМП, опухоли были меньшего объема и отмечали увеличение продолжительности жизни
животных. Показано, что М протеин проявляет антиангиогенные свойства и обладает способностью индуцировать апоптоз.
Выводы: М протеин ВВС ингибирует рост глиомы in и in. На этой основе может быть разработана потенциально новая
биотерапевтическая стратегия для лечения пациентов с глиомами.